Bodies of Stone in the Media, Visual Culture and the Arts - Violi, Alessandra (Amsterdam University Press, 2020)
Cover -- Table of Contents -- Introduction -- Learning from Stone -- Alessandra Violi, Barbara Grespi, Andrea Pinotti and Pietro Conte -- I. Statue: The Imaginary of Uncertain Petrification -- 1. Theatre and Memory: The Body-as-Statue in Early Modern Culture -- Greta Perletti -- 2. Translated Bodies: A 'Cartographic' Approach -- Silvia Romani -- 3. Pantomime in Stone: Performance of the Pose and Animal Camouflage -- Barbara Grespi -- 4. Animated Statues and Petrified Bodies: A Journey Inside Fantasy Cinema -- Michele Bertolini -- 5. The Ephemeral Cathedral: Bodies of Stone and Configurations of Film -- Vinzenz Hediger -- II. Matter: Size, Hardness, Duration -- 1. Bodies That Matter: Miniaturisation and the Origin(s) of 'Art' -- Michele Cometa -- 2. Brancusi's 'Sculpture for the Blind' -- Elio Grazioli -- 3. Cinema, Phenomenology and Hyperrealism -- Pietro Conte -- 4. Ephemeral Bodies: The 'Candles' of Urs Fischer -- Cristina Baldacci -- 5. The Celluloid and the Death Mask: Bazin's and Eisenstein's Image Anthropology -- Antonio Somaini -- III. Corpse: Fossils, Auto-Icons, Revenants -- 1. Funeral Eulogy: Post-Mortem Figures and Redeemed Bodies, in Images* -- Luisella Farinotti -- 2. On Jack Torrance As a Fossil Form -- Barbara Le Maître -- 3. Technical Images and the Transformation of Matter in Eighteenth-Century Tuscany -- Anna Luppi -- 4. Glass, Mixed Media, Stone: The Bodily Stuffs of Suspended Animation -- Alessandra Violi -- 5. Bodies' Strange Stories: Les Revenants and The Leftovers -- Luca Malavasi -- IV. Monument: Embodying And Grafting -- 1. The Impassibly Fleshly, the Statue of the Impossible -- Filippo Fimiani -- 2. Frozen into Allegory: Cleopatra's Cultural Survival -- Elisabeth Bronfen -- 3. The Orphan Image -- Federica Villa -- 4. The Well-Tempered Memorial: Abstraction, Anthropomorphism, Embodiment -- Andrea Pinotti.